Computer Vision and Computer Graphics. Theory and Applications International Conference VISIGRAPP 2007, Barcelona, Spain, March 8-11, 2007, Revised Selected Papers - Braz, José; Ranchordas, AlpeshKumar; Araújo, Hélder J.; Madeiras Pereira, Joao (Communications in Computer and Information Science, 2008)
This book constitutes the refereed proceedings of the International Conference on Computer Vision and Computer Graphics Theory and Applications, Visigrapp 2007, held in Barcelona, Spain, in March 2007. The 18 revised full papers presented were carefully reviewed and selected from a total of 382 submissions. The papers are organized in topical sections on geometry and modeling; animation and simulation; interactive environments; image formation and processing; image analysis; image understandung as well as motion, tracking and stereo vision.